Multi-Harmonic Currents Control Strategy for Five-Phase Permanent Magnet Machine With Non-Sinusoidal Back-EMF - J. Y. Zhang; S. J. He; K. Wang (IEEE Access)
This paper describes an optimal torque per peak current control method for a five-phase permanent magnet (PM) machine considering both $3^{rd}$ and $5^{th}$ harmonic currents. These optimal ratios to the fundamental component are analytically derived to maximize the output torque. It is found that except for the $3^{rd}$ harmonic current contributing to the output torque, the $5^{th}$ harmonic current can also produce the additional positive torque. However, the $5^{th}$ harmonic is zero sequence component for the five-phase machines, which does not exist in the phase windings. Hence, the neutral point is required to connect the middle point of the DC link capacitors for constructing flowing path. The conventional vector space decomposition (VSD) control is extended to zero sequence sub-plane, which can quantitatively control $5^{th}$ harmonic current. For a prototype five-phase PM machine, the average torque can be increased by 21.4% with $3^{rd}$ harmonic current injection. Meanwhile, 10.7% additional positive torque is achieved together with $3^{rd}$ and $5^{th}$ harmonic injection. The torque ripple remains similar to that without harmonics injection. Finally, the experiments are given to demonstrate the theoretical analysis.